The Extent to Which the Textbooks of Islamic Culture for the Secondary Stage (11-12) in the Hashemite Kingdom of Jordan Include the Types of Crime - Alhjooj, Abedalkader Saleh Abedalkader (Journal of Educational and Psychological Sciences, 2020)
This study aimed at identifying the extent to which the textbook of Islamic culture (the first level, the second level, and the third level) include the types of crime in the Hashemite Kingdom of Jordan. The study used the descriptive analytical approach. The study tool which was developed consisted of (44) crimes and was divided into five domains according to the crime type. The study sample consisted of all the textbooks of Islamic culture for the secondary stage (the first level, the second level, and the third level). The study results showed that the crime total frequency was (147) distributed to the five domains. The economical crimes domain was in the first place with a frequency of (68) and a percentage of (46%). The societal violence crimes were in the second rank with a frequency of (29) and a percentage of 20%. The sexual crimes and political crimes were in the third rank with a percentage of (16%), while the electronic crimes were in the last rank with a percentage of (2%). In the light of the results, the study concluded with a number of recommendations and suggestions about including more crimes and the proper solutions for them.